Simplified Constellation Architecture for the Libration Point Satellite Navigation System. (5th April 2016) - Zhang, Lei; Xu, Bo
Abstract : In this paper, a simplified constellation architecture consisting of only two navigation satellites located around the Earth-Moon L 1, 2 libration points is obtained for the Universe Lighthouse. In order to determine the feasible constellations that can achieve continuous global coverage for lunar orbits, an exhaustive search over all possible combinations of libration point orbits is performed first. With the use of a fitting procedure, amplitude relations between the feasible L 1 and L 2 libration point orbits are derived by polynomial interpolation. After that, a cislunar navigation simulation is conducted to verify the navigation performance of the candidate two-satellite constellations. The final Monte Carlo simulation results indicate that the simplified system is available for cislunar navigation and the best accuracy of a few tens of metres can be achieved for both the trans-lunar cruise phase and lunar orbit phase.